Clinical practice insight: vasoactive-inotropic drugs do not impede early enteral nutrition in pediatric ECMO support - Ren, Ye; Zhou, Run; Dang, Hongxing; Fu, Yueqiang; Liu, Chengjun; Li, Jing (Frontiers in Nutrition, 2025)
ObjectiveTo evaluate whether vasoactive-inotropic drug use impedes the early initiation of enteral nutrition (EN) and affects energy intake adequacy in pediatric patients receiving extracorporeal membrane oxygenation (ECMO) support.MethodsA prospective observational cohort study was conducted among pediatric ECMO patients between June 2018 and June 2024. Patients were categorized into early (≤ 48 h) and delayed (> 48 h) EN initiation groups, and into energy-deficient (< 30% of energy target) and non-deficient (≥ 30%) groups based on daily EN energy intake during the first five ECMO days. Vasoactive-Inotropic Score (VIS), PRISM III score, EN interruptions, and energy intake adequacy were analyzed. Spearman correlation and Cohen’s d were used to explore associations between VIS and EN intake. A support vector machine (SVM) model was used to identify predictors of energy intake status.ResultsA total of 64 patients were included, with 43 (67.2%) receiving EN within 48 h. VIS did not significantly differ between early and delayed EN groups. Delayed EN was associated with higher PRISM III scores (P = 0.037), lower EN energy intake (P < 0.001), and more frequent EN interruptions (P = 0.028). Among patients with EN intake <30% of the target, VIS was significantly higher (P < 0.05). VIS on days 1 and 2 were the top predictors in the SVM model (25.7% and 27.4%, respectively).ConclusionVasoactive-inotropic drug use does not impede the early initiation of EN in pediatric ECMO patients. However, higher VIS in the initial 48 h is associated with suboptimal energy delivery. These findings suggest that while EN can be started early despite vasoactive support, closer monitoring of hemodynamic status is warranted to optimize nutritional adequacy.